Effect of Textile Factory effluents upon concentrations of Some Trace Elements in Water of the Euphrates River at the center of Al-Nasiriyah city Southern Iraq - ojs_admin (مجلة علوم ذي قار, 2019)
The present study deal with the effect of the effluents from of Textile Factory, in concentrations of six trace elements ( Cadmium, copper, Nickel, Lead, Zinc, and Manganese) in water of Euphrates river at the center of AlNasiriyah south of